1989
DOI: 10.3171/jns.1989.71.5.0665
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinicopathological features of meningioma

Abstract: The incidence of intracranial meningioma in Manitoba, Canada, was reviewed from 1980 through 1987. During that time, 193 tumors were diagnosed, with a male:female ratio of 1:2. This occurrence corresponded to crude incidence rates of 2.3/100,000 for all meningiomas and 0.17/100,000 for malignant meningiomas. Among malignant meningiomas, the male:female ratio was 1:1. The age-specific annual incidence rate increased with age up to the eighth decade where it peaked at 8.4/100,000. The distribution of histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
166
5
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(201 citation statements)
references
References 40 publications
14
166
5
16
Order By: Relevance
“…One older study from 1989 reported a crude incidence rate of malignant meningiomas of 0.17 per 100 000 in Manitoba, Canada, which was lower than that found in our study. 9 Our study demonstrates that the incidence of WHO II meningiomas is increasing, while the incidence of WHO III meningiomas is decreasing. No prior studies have evaluated temporal trends in WHO II and III meningiomas for comparison.…”
Section: Kshettry Et Al: Epidemiology Of High-grade Meningiomasmentioning
confidence: 79%
See 2 more Smart Citations
“…One older study from 1989 reported a crude incidence rate of malignant meningiomas of 0.17 per 100 000 in Manitoba, Canada, which was lower than that found in our study. 9 Our study demonstrates that the incidence of WHO II meningiomas is increasing, while the incidence of WHO III meningiomas is decreasing. No prior studies have evaluated temporal trends in WHO II and III meningiomas for comparison.…”
Section: Kshettry Et Al: Epidemiology Of High-grade Meningiomasmentioning
confidence: 79%
“…6,8,9 When stratified by age, females had the highest incidence rate ratios for meningiomas of all WHO grades during middle ages (35 -64 y), Kshettry et al: Epidemiology of high-grade meningiomas whereas males had a higher incidence in older ages (≥75 y). An increase in risk excess in middle-aged women has been demonstrated with WHO I meningiomas in prior studies as well.…”
Section: Kshettry Et Al: Epidemiology Of High-grade Meningiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Todavia, faltam evidências definitivas que esclareçam o verdadeiro papel de todos estes fatores na gênese dos meningiomas. Sua incidência é de 2:100000 23 . Em grandes séries compreendem aproximadamente 20% de tumores intracranianos operados 10 .…”
Section: Discussionunclassified
“…The clinical symptoms usually depend on the involved anatomic site, but many of them are found incidentally. The three most common symptoms are headaches, mental status changes, and paresis (8). Aggression and hallucination are seen in association with a basal frontal lesion and may mimic psychotic syndromes like hypomania and schizophrenia, particularly if the tumor encroaches on the third ventricle and adjacent structures (1,2).…”
Section: Discussionmentioning
confidence: 99%